Political movements and violence in Central America - Brockett, Charles D., 1946- (Cambridge studies in contentious politics., 2005)
Charles Brockett offers an in-depth analysis of the confrontation between popular movements and repressive regimes in Central America during the three decades beginning in 1960, particularly in El Salvador and Guatemala.